Tantangan Guru dalam Memberikan Pendidikan Kecakapan Hidup bagi Siswa Down Syndrome SLB Samudra Terra Athena - Alfiatul Hasanah; Nova Estu Harsiwi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Students with Down syndrome have developmental characteristics that differ from typical students. In such cases, the educational approach should not only focus on academic aspects but also on life skills education. In teaching life skills, teachers must adapt to each child's individual abilities. However, in practice, teachers often face various challenges. This study aims to describe the challenges faced by teachers at Terra Athena Special Needs School (SLB) in providing life skills education for students with Down syndrome, as well as the strategies used to overcome these challenges. This research uses a qualitative case study approach with data collection techniques including interviews, observations, and documentation. Data analysis was conducted using triangulation techniques to enhance data validity. The results show that teachers face several challenges such as the wide range of student abilities, students' tendencies to be absorbed in their own world, limited facilities, and the need for more time to carry out each activity. The strategies implemented include positive reinforcement and individualized approaches, the use of visual media and concrete tools, collaboration with therapists and parents, and a boarding program for students.